Epigenetics in Cancer: The Myelodysplastic Syndrome as a Model to Study Epigenetic Alterations as Diagnostic and Prognostic Biomarkers - Fernandez, Teresa de Souza; Mencalha, André; Fernandez, Cecília de Souza (IntechOpen, 2012)
None